1999
DOI: 10.1074/jbc.274.47.33764
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Catalytic Activities of the Two Domains of the Allene Oxide Synthase-Lipoxygenase Fusion Protein of the CoralPlexaura homomalla

Abstract: The conversion of fatty acid hydroperoxides to allene epoxides is catalyzed by a cytochrome P450 in plants and, in coral, by a 43-kDa catalase-related hemoprotein fused to the lipoxygenase that synthesizes the 8R-hydroperoxyeicosatetraenoic acid (8R-HPETE) substrate. We have expressed the separate lipoxygenase and allene oxide synthase (AOS) domains of the coral protein in Escherichia coli (BL21 cells) and purified the proteins; this system gives high expression (1.5 and 0.3 mol/liter, respectively) of catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
102
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(104 citation statements)
references
References 42 publications
1
102
1
Order By: Relevance
“…During these reactions, cAOS inactivates irreversibly after tens of seconds (7). Although the proposed mechanism of allene oxide synthases involves homolytic cleavage of hydroperoxide, many hemoproteins react with organic hydroperoxides by a mixture of homolysis and heterolysis (18).…”
Section: Discussion Stoichiometric Oxidation Of Coral Aos By Peracetimentioning
confidence: 99%
See 3 more Smart Citations
“…During these reactions, cAOS inactivates irreversibly after tens of seconds (7). Although the proposed mechanism of allene oxide synthases involves homolytic cleavage of hydroperoxide, many hemoproteins react with organic hydroperoxides by a mixture of homolysis and heterolysis (18).…”
Section: Discussion Stoichiometric Oxidation Of Coral Aos By Peracetimentioning
confidence: 99%
“…HpETE) in the intact fusion protein, as well as when it is expressed separately, but it does not exhibit catalase activity (7). Evidence from sequence and spectroscopy has confirmed that the similarity of coral AOS to catalase includes tyrosinate axial ligation to heme iron (6,8).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The coral LOX domain has sequence similarities to other mammalian and plant lipoxygenases; the coral AOS domain has significant sequence homology to catalase, albeit with very low (30%) sequence identity (3). It has been shown recently that coral AOS cannot disproportionate hydrogen peroxide like catalases, and catalase cannot convert 8R-HPETE to allene oxide (4).…”
mentioning
confidence: 99%